2020
DOI: 10.1515/jpem-2019-0413
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of 85 patients with urea cycle disorders: one center experience, three new mutations

Abstract: ObjectivesUrea cycle disorders (UCDs) are rare hereditary diseases. This study was conducted to help identify the characteristics of UCDs in Turkey.MethodsThe primary outcome was to determine patient characteristics. Investigating the relationships between the patient outcomes and ammonia levels were the secondary outcomes. Eighty five patients from 79 families, diagnosed with UCD at a single metabolic referral center between 1979 and 2017, were included. Clinical and laboratory data were retrieved retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
2
1
Order By: Relevance
“…In a previous single-centre cohort study from France, neonatal presentation was found in 30% of total OTCD patients, while in our study, this was reported in 19% of patients in France [14]. Likewise, a single centre study from Turkey revealed that almost 10% of patients had neonatal presentation, whereas, this is reported as 12% in Turkey in our study [33]. Neonatal presentation was reported only in 7% of the UK patients in our survey.…”
Section: Discussioncontrasting
confidence: 61%
“…In a previous single-centre cohort study from France, neonatal presentation was found in 30% of total OTCD patients, while in our study, this was reported in 19% of patients in France [14]. Likewise, a single centre study from Turkey revealed that almost 10% of patients had neonatal presentation, whereas, this is reported as 12% in Turkey in our study [33]. Neonatal presentation was reported only in 7% of the UK patients in our survey.…”
Section: Discussioncontrasting
confidence: 61%
“…rough the research on the related principles of the consumer behavior conditioning theory, it is proposed to strengthen the brand loyalty from the perspective of the classical conditioning principle. From the principle of operant conditioning, the behavioral loyalty to the brand is strengthened, and then, the brand loyalty of consumers is formed [4]. Lototskyy et al conducted an in-depth discussion on the mechanism of brand extension and further expounded consumers' trust and loyalty to the brand's original products from the aspects of learning theory, ratchet effect theory, risk theory, and demand hierarchy theory; through the low-cost transfer of brand extension to extended products, this almost recognized but lacking detailed analysis point of view has been analyzed, which has laid a theoretical foundation for the related research on brand extension [5].…”
Section: Literature Reviewmentioning
confidence: 99%
“…CRRT is particularly effective in maple syrup disease, organic acidemia with hyperammonemia, and inborn metabolism in urea cycle disorder [ 25 28 ]. Higher peak ammonia levels during hyperammonemia episodes are associated with worse survival rates, and the duration of coma before dialysis is negatively associated with cognitive outcomes [ 26 , 29 ]. The rate of ammonia clearance with CRRT has been associated with improved outcomes [ 25 – 30 ].…”
Section: Discussionmentioning
confidence: 99%